Antioxidant and trombolitic activity of etanol extract and fractions of carica culver (Carica pubescens) in vitro - Pratiwi, Yunia; Indrayati, Ana; Mardiyono, Mardiyono (Surya Hijau Manfaat, 2025)
The prevalence of degenerative diseases arising from cell damage and free radicals continues to increase. The reactivity of oxidant compounds that exceed the limit can form a chain reaction capable of damaging parts of blood vessel cells that cause thrombolysis. Carica skin waste (Carica pubescens) has not been widely utilized, carica skin has the potential to have the ability as an antioxidant and thrombolytic. This study aims to determine the potential antioxidant and thrombolytic activity of carica peel. Carica peel samples were extracted by remaceration method using 70% ethanol and then fractionated with n-hexane, ethyl acetate, and water solvents. Antioxidant activity testing was carried out using the DPPH (2.2 Diphenyl-1-picrylhydrazyl) method and thrombolytic activity with the clot lysis method. The results showed that the ethyl acetate fraction had the highest antioxidant activity compared to ethanol extract and other fractions with an IC50 value of 37.04 ppm with an AAI value of 0.54. The thrombolytic activity test of ethyl acetate fraction is also the highest thrombolytic agent with clot lysis value reaching 46.06% close to the clot lysis value of nattokinase positive control of 52.39%.